Relevance of innovativeness in enhancing productivity among Nigeria’s entrepreneurs - Oladipo, Ganiyu Taiwo; Omolekan, Olushola Joshua; Olota, Oluwayomi Omotayo; Abogunrin, Abiodun Peter (Program Pascasarjana Universitas Negeri Yogyakarta, 2026)
This paper examines the relationship between innovativeness and productivity among entrepreneurs. Specifically, it examined the impact of new product development, market exploration, and technological advancements on entrepreneurs’ productivity. A survey research design was adopted with a population of 1,416 registered SMEs in Nigeria. A total of 312 sample sizes were administered a structured questionnaire. Data collected was analyzed using PLS-SEM. Findings revealed that market exploration has the strongest effect on entrepreneurs’ productivity, followed by new product development and technology advancement. It concluded that innovativeness is significantly vital for entrepreneurs' productivity of selected registered SMEs. It is therefore recommended that SME owners in Kwara state enhance their entrepreneurs' productivity by focusing on adopting unique technology advancements, supporting new product development, and engaging in market exploration, which can ensure that innovativeness is met, thereby helping to enhance entrepreneurs' productivity.